2010
DOI: 10.1002/ejoc.200901359
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent C‐Alkylation Reactions of Aromatic Aldimines with Trialkylboranes Reagents

Abstract: The one-pot three-component reaction of an aryl aldehyde, an arylamine, and a trialkylborane in the presence of hydrogen peroxide afforded the alkylated arylamines 1 in good

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…A three component reaction with an aldehyde, an amine and a trialkylborane as a multifunctional reagent has also been reported [88]. The borane exhibits a triple role in this reaction: it serves as a Lewis acid catalyst and facilitates imine formation and further activates the imine towards radical addition by coordination.…”
Section: Addition To Aliphatic Iminium Ionsmentioning
confidence: 99%
“…A three component reaction with an aldehyde, an amine and a trialkylborane as a multifunctional reagent has also been reported [88]. The borane exhibits a triple role in this reaction: it serves as a Lewis acid catalyst and facilitates imine formation and further activates the imine towards radical addition by coordination.…”
Section: Addition To Aliphatic Iminium Ionsmentioning
confidence: 99%
“…under our standard conditions, and a 58% yield of alkylated product 3a could be obtained (Scheme a). In contrast, employing the H 2 O 2 reaction system in which the alkylborane could be easily oxidized to alkyl radical intermediates, could not afford the desired product 3a (Scheme b). These findings demonstrated that a free radical process was not involved in this transformation.…”
Section: Resultsmentioning
confidence: 98%
“…In the presence of oxygen, Et 3 B efficiently produces ethyl radicals that initiate radical chain processes, even at low temperature . Moreover, it can also act as a chain transfer reagent since it undergoes homolytic substitution with aminyl radicals (such an intermediate aminyl radical is expected in our proposed cascade; see Scheme ). Based on the tin-free conditions developed in our group for the radical carboazidation, we first tried to prepare indoline 2a from azide 1a and iodide 4 in the presence of an excess of Et 3 B in EtOH/H 2 O.…”
mentioning
confidence: 93%